Enhanced coagulation and microplastic removal by multiple factor coupling: Nonlinear interaction mechanism and synergistic effect - Jiahui Mi; Junping Lu; Tingxi Liu; Zhuo Li; Shixin Han (Journal of Environmental Chemical Engineering, 2026)

Molecular disruption of neuroinflammatory and metabolic pathways mediates triclosan-induced depressive-like behavior in zebrafish - Danting Wang; Junping Liu; Ruixue Zhou; Bing Han; Chunxia Chen; Wentong Meng; Li Qin; Limei Sun; Bin Tan; Chunyan Huang (Toxicology and Applied Pharmacology, 2026)

Assessing the impact of green certificate market transformation on China's carbon market under a multi-market coupling framework - Yang Yang; Han Shen; Wei Liu; Yiqi Wang; Junping Ji; Daojing He; Qisheng Huang (Journal of Cleaner Production, 2026)

Highly stable colorimetric hydrogel indicators based on β-cyclodextrin-Assisted Co-pigmentation and machine learning for real-time pork freshness monitoring - Xiaoxue Han; Shuaibo Zhang; Junping Yin; Shasha Zhang; Muhammad Waqas; Yuye Zhong; Xianwen Ke; Xinghai Liu (Food Control, 2026)

Adsorption of weak polar zearalenone mycotoxins from water environment by tourmaline mineral powder of spontaneous electrical polarization properties - Na Zhang; Xiaoyu Han; Yinyuan Lei; Junping Meng; Hong Zhang; Jinsheng Liang (Environmental Research, 2025)

Enhanced conductivity and energy storing performances of 3D bimetallic conductive metal-organic frameworks based on linear π-conjugated thiazole for supercapacitors - Chungui Wang; Yichen He; Junping Xie; Siyi Wang; Yingjun Chen; Xu Yang; Yong Pei; Naien Shi; Mong-Feng Chiou; Linghai Xie; Xiaomiao Feng; Min Han (Chemical Engineering Journal, 2025)

Removal of Cu2+ and Cd2+ by modified chitosan hydrogel - Heyu Sun; Junping Han; Chunyan Kong; Jiang Zhan; Li Chen; Yiping Zhao (Journal of Water Process Engineering, 2025)

Bryophytes adapt to open-pit coal mine environments by changing their functional traits in response to heavy metal-induced soil environmental changes - Yu Han; Jin Kou; Baichuan Jiang; Junping Li; Changchang Liu; Shaogang Lei; Hongxing Xiao; Chao Feng (Journal of Hazardous Materials, 2025)

Distribution of mercury and methylmercury in ice-water-sediments in lakes during the freezing period under the influence of ice cover - Yunxi Zhao; Shengnan Zhao; Xiaohong Shi; Junping Lu; Zhimou Cui; Fan Zhang; Hui Zhang; Jinda Zhang; Yue Han (Environmental Pollution, 2024)

Acetate-based ionic liquid immobilized Fe-MIL-101-NH2: A highly efficient heterogeneous catalyst for the conversion of CO2 into oxazolidinones with N-aryl epoxy amines - Junping Niu; Guanghui Wang; He Qiao; LiGang Yan; Jiakai Wu; Yuanyuan Gao; Limin Han; Ning Zhu (Journal of Environmental Chemical Engineering, 2024)

Highly efficient recovery of Zn (II) from zinc-containing wastewater by tourmaline tailings geopolymers to in-situ construct nanoscale ZnS for the photodegradation of tetracycline hydrochloride - Zhixiao Ren; Caihong Zhang; Jinpeng Chen; Hong Zhang; Junping Meng; Xiaoyu Han; Jinsheng Liang (Environmental Research, 2024)

In vivo EPID-based daily treatment error identification for volumetric-modulated arc therapy in head and neck cancers with a hierarchical convolutional neural network: a feasibility study - Yiling Zeng; Heng Li; Yu Chang; Yang Han; Hongyuan Liu; Bo Pang; Jun Han; Bin Hu; Junping Cheng; Sheng Zhang; Kunyu Yang; Hong Quan; et al. (Physical and Engineering Sciences in Medicine, 2024)

The biotic effects of lignite on humic acid components conversion during chicken manure composting - Yumeng Wang; Ziyi Han; Junping Liu; Caihong Song; Zimin Wei (Bioresource Technology, 2024)

Identification of pollution source and prediction of water quality based on deep learning techniques - Junping Wang; Baolin Xue; Yuntao Wang; Yinglan A; Guoqiang Wang; Dongqing Han (Journal of Contaminant Hydrology, 2024)

A digital platform for One-Pot signal enhanced foodborne pathogen detection based on mesophilic argonaute-driven polydisperse microdroplet reactors and machine learning - Junping Wen; Minjie Han; Niu Feng; Guoxun Chen; Feng Jiang; Jianhan Lin; Yiping Chen (Chemical Engineering Journal, 2024)

Immune-Ageing Evaluation of Peripheral T and NK Lymphocyte Subsets in Chinese Healthy Adults - Zhenghu Jia; Zhiyao Ren; Dongmei Ye; Jiawei Li; Yan Xu; Hui Liu; Ziyu Meng; Chengmao Yang; Xiaqi Chen; Xinru Mao; Xueli Luo; Zhe Yang; et al. (Phenomics, 2023)
Ageing is often accompanied with a decline in immune system function, resulting in immune ageing. Numerous studies have focussed on the changes in different lymphocyte subsets in diseases and immunosenescence. The change in immune phenotype is a key indication of the diseased or healthy status. However, the changes in lymphocyte number and phenotype brought about by ageing have not been comprehensively analysed. Here, we analysed T and natural killer (NK) cell subsets, the phenotype and cell differentiation states in 43,096 healthy individuals, aged 20–88 years, without known diseases. Thirty-six immune parameters were analysed and the reference ranges of these subsets were established in different age groups divided into 5-year intervals. The data were subjected to random forest machine learning for immune-ageing modelling and confirmed using the neural network analysis. Our initial analysis and machine modelling prediction showed that naïve T cells decreased with ageing, whereas central memory T cells (Tcm) and effector memory T cells (Tem) increased cluster of differentiation (CD) 28-associated T cells. This is the largest study to investigate the correlation between age and immune cell function in a Chinese population, and provides insightful differences, suggesting that healthy adults might be considerably influenced by age and sex. The age of a person's immune system might be different from their chronological age. Our immune-ageing modelling study is one of the largest studies to provide insights into ‘immune-age’ rather than ‘biological-age’. Through machine learning, we identified immune factors influencing the most through ageing and built a model for immune-ageing prediction. Our research not only reveals the impact of age on immune parameter differences within the Chinese population, but also provides new insights for monitoring and preventing some diseases in clinical practice.

Recycling of iron ore tailings into magnetic nanoparticles and nanoporous materials for the remediation of water, air and soil: a review - Xiaoyu Han; Fei Wang; Yan Zhao; Junping Meng; Guangyan Tian; Lijuan Wang; Jinsheng Liang (Environmental Chemistry Letters, 2023)

Comparative Transcriptomic Analysis Reveals the Regulatory Mechanism of Terpene Trilactones Improvement by Exogenous Methyl Jasmonate in Ginkgo biloba - Junping Tan; Muxian Han; Dun Mao; Shuiyuan Cheng; Jiabao Ye; Xiaomeng Liu; Xian Zhang; Jiarui Zheng; Feng Xu; Zexiong Chen; Weiwei Zhang; Yongling Liao (Plant Molecular Biology Reporter, 2022)

Phylogenetic, evolutionary, and biogeographic origin of the genus Sheathia (Batrachospermales, Rhodophyta) - Jinfen Han; Fangru Nan; Jia Feng; Junping Lü; Qi Liu; Xudong Liu; Shulian Xie (Journal of Oceanology and Limnology, 2022)

Mechanical characteristics and freeze–thaw damage mechanisms of mode-I cracked sandstone from the Three Gorges Reservoir region under different chemical solutions - Tielin Han; Zhihui Li; Junping Shi; Xiaoshan Cao (Arabian Journal of Geosciences, 2021)

Affinities of freshwater “Chantransia” stage algae (Rhodophyta) from China based on molecular and morphological analyses - Jinfen Han; Fangru Nan; Jia Feng; Junping Lü; Qi Liu; Xudong Liu; Shulian Xie (Journal of Oceanology and Limnology, 2021)

Microbiome technology empowers the development of traditional Chinese medicine - Hongtao Liu; Junping Zheng; Hsin-Chih Lai; Baifei Hu; Lin Zhu; Elaine Lai-Han Leung; Hong Wei (Science China Life Sciences, 2020)

Mechanism Damage to Mode-I Fractured Sandstone from Chemical Solutions and Its Correlation with Strength Characteristics - Tielin Han; Junping Shi; Yunsheng Chen; Xiaoshan Cao (Pure and Applied Geophysics, 2019)

Fracturing and Damage to Sandstone Under Coupling Effects of Chemical Corrosion and Freeze–Thaw Cycles - Tielin Han; Junping Shi; Xiaoshan Cao (Rock Mechanics and Rock Engineering, 2016)

Transplantation of mesenchymal stem cells into the renal medulla attenuated salt-sensitive hypertension in Dahl S rat - Junping Hu; Qing Zhu; Min Xia; Tai L. Guo; Zhengchao Wang; Pin-Lan Li; Wei-Qing Han; Fan Yi; Ningjun Li (Journal of Molecular Medicine, 2014)